Political Support in Times of Personalized Politics. A Qualitative Inquiry of French Citizens' Representations About Political Actors and the Political Regime - Dolez, Charlotte (Frontiers in Political Science, 2021)
This article investigates how citizens speak about representative democracy and questions their perceptions of representation and of the democratic regime they live in, by mobilizing the distinction between diffuse and specific support, in a context of personalized politics. It shows that political actors and their performances are at the core of citizens' perceptions. I investigate citizens' representations of the political field through an original qualitative fieldwork, composed of couple interviews with French citizens, under the Sarkozy presidency. Studies about the political support of citizens often mobilize quantitative surveys to measure the degree of support and satisfaction. I rather choose the qualitative approach to grasp perceptions of political field through discussions about political and societal issues. Couple interviews offer an adequate framework to observe political opinions that are built in daily life. Representations of the political field are mainly dominated by the role of political actors. Political parties and institutions are rarely mentioned. Politicians are systematically held accountable, and are often criticized in citizens' discussions. The existing literature has often distinguished specific and diffuse support. My analysis tends to show that the weakness of the former through personalization can undermine the support for the regime. However, alternatives to representative democracy remain underexplored and even not considered. Overall, these representations depend on sociopolitical factors, such as political convictions or social backgrounds.